Photographic Evidence of Red Fox (Vulpes vulpes) in Lansdowne Forest Division, Uttarakhand - Umariya, Siddhant; Pawar, Devavrat; Singh, Vaibhav; Bakshi, Soumya; Antil, Jyoti; Singh, A. K.; Bopanna, I. P. (Indian Forester, 2020)
No Abstract.